2017
DOI: 10.1103/physrevd.96.095007
|View full text |Cite
|
Sign up to set email alerts
|

Probing light mediators at ultralow threshold energies with coherent elastic neutrino-nucleus scattering

Abstract: Light neutral mediators, with mass 1 GeV, are common features of extensions to the Standard Model (SM). Current astrophysical and terrestrial experiments have constrained the model parameter space, and planned experiments around the world promise continued improvement in sensitivity. In this paper we study the prospects for probing light neutral mediators using terrestrial stopped pion and reactor sources in combination with ultra-low threshold nuclear and electron recoil detectors. We show that the coherent n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 58 publications
0
45
0
Order By: Relevance
“…For example, alterations are expected at high recoil energies of neutrino-induced interactions at direct DM detection searches [39] which on the other hand may be limited by the current uncertainties of the Atmospheric and DSNB neutrinos. Models involving light mediators are well testable at CEνNS searches and may offer a key solution to LMA-Dark [151,159] as well as implications to DM searches [28,133] and to the neutrino floor [40]. In the same spirit, combined analyses of oscillation and CEνNS data [15,18] concluded that the LMA-D solution is excluded at 3.1σ (3.6σ) for NSI with up (down) quarks.…”
Section: Connection Of Ceνns With Dark Matter Clfv Processes Andmentioning
confidence: 96%
“…For example, alterations are expected at high recoil energies of neutrino-induced interactions at direct DM detection searches [39] which on the other hand may be limited by the current uncertainties of the Atmospheric and DSNB neutrinos. Models involving light mediators are well testable at CEνNS searches and may offer a key solution to LMA-Dark [151,159] as well as implications to DM searches [28,133] and to the neutrino floor [40]. In the same spirit, combined analyses of oscillation and CEνNS data [15,18] concluded that the LMA-D solution is excluded at 3.1σ (3.6σ) for NSI with up (down) quarks.…”
Section: Connection Of Ceνns With Dark Matter Clfv Processes Andmentioning
confidence: 96%
“…Although only new vector mediators are considered here, one can introduce other types of mediators and associated couplings, e.g., the mediator could be of scalar and/or pseudoscalar type [13,20,22].…”
Section: Coherent Elastic Neutrino-nucleus Scatteringmentioning
confidence: 99%
“…Such limits only apply to mediators with masses sufficiently above the momentum transfer scale of the interaction. Some studies have placed bounds on simplified models including a light Z 0 [11,[21][22][23][24], but they all assume a direct coupling to both neutrinos and first-generation quarks rather than indirect couplings induced from mixing.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several previous studies of NSI at nuclear reactors [19,[24][25][26][27]. The aforementioned reactor experiments operate at power ranges from ∼MW-GW, and a range of distance from the reactor core from a few meters to a few tens of meters.…”
Section: B Reactorsmentioning
confidence: 99%